Development of Information System Management Customer Satisfaction Using the Simple Additive Weighting Method and Website-Based Google Maps API at ISP XYZ - Ahmad Habib; Putra Aditya Nova; Ardy Januantoro (SISFORMA, 2021)
Internet Service Provider XYZ is a service company that provides a variety of Internet  service  package  products,  cloud data, communication networks, and complete installations,  as  well  as  various  local  and international  TV  channel  service  packages interactively  using  fiber  optic  technology. However,  over  time,  problems  arose,  where many  customers  complained  about  the troubleshooter service management provided by the ISP, for example, related to reports of disturbances  from  customers,  the  length  of time  in  handling  disturbances,  the  lack  of clarity  of  officers  who  handled  disturbances and so on which led to a decrease in the level of  customer  satisfaction.  To  deal  with  these problems,  researchers  developed  a  customer satisfaction  management  information  system by  applying  the  Simple  Additive  Weighting method supported by a website-based google maps API to solve the problems being faced by  ISP  XYZ.  The  results  of  the  system development  are  expected  to  facilitate  and speed  up  the  handling  of  problems  that  are being experienced by customers and with the application  of  the  SAW  method  can  easily find  out  the  level  of  customer  satisfaction  at the XYZ ISP.